2009
DOI: 10.1111/j.1600-0560.2008.01214.x
|View full text |Cite
|
Sign up to set email alerts
|

An infiltrative variant of non‐neural granular cell tumor: a case report

Abstract: Dermal non-neural granular cell tumors are rare tumors of indeterminate lineage that typically present as well-circumscribed tumors with nuclear pleomorphism and mitotic activity. We describe a dermal non-neural granular cell tumor with a distinctive growth pattern with granular cells interspersed between collagen bundles. This asymptomatic papule arose on the scapula of a 46-year-old woman and consisted of a mixture of epithelioid and spindled granular cells. The immunohistochemical characteristics were simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Positive reactivity is seen with CD68, NKI/C3, NSE, and factor XIIIa. 7,8 The histomorphological appearance and absence of actin, desmin, and/or caldesmon immunoreactivity effectively exclude leiomyoma and leiomyosarcoma. 8,9 Basal cell carcinomas with granular cell change are usually of the nodular type with an immunohistochemical profile demonstrating reactivity with cytokeratins.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Positive reactivity is seen with CD68, NKI/C3, NSE, and factor XIIIa. 7,8 The histomorphological appearance and absence of actin, desmin, and/or caldesmon immunoreactivity effectively exclude leiomyoma and leiomyosarcoma. 8,9 Basal cell carcinomas with granular cell change are usually of the nodular type with an immunohistochemical profile demonstrating reactivity with cytokeratins.…”
Section: Discussionmentioning
confidence: 98%
“…7,8 The histomorphological appearance and absence of actin, desmin, and/or caldesmon immunoreactivity effectively exclude leiomyoma and leiomyosarcoma. 8,9 Basal cell carcinomas with granular cell change are usually of the nodular type with an immunohistochemical profile demonstrating reactivity with cytokeratins. 10 Granular cell atypical fibroxanthoma usually presents as a rapidly enlarging dome-shaped nodule and typically located on sun-exposed areas of elderly patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…d Barium study noted a 4-cm stricture oral cavity, brain, and pituitary showed no reactivity to S-100 or neuron-specific enolase. More recently, several cases of cutaneous granular cells of non-neural origin have been reported [5][6][7][8]. Their propensity for being multricentric has been reported in as many as 10-15% of cases [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these tumors are benign, although 2-4% have a malignant potential. Electron microscopy and immunohistochemical investigations in the recent past have attributed their origin to Schwann cells, although there has been some controversy with this regard [3][4][5][6][7][8]. On review of literature, to date, less than 300 cases have been described worldwide.…”
Section: Introductionmentioning
confidence: 94%